2021
DOI: 10.3390/safety7020049
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness in Pilots Correlates with Electrodermal Stability: Study on Simulated Flights under Social Stress

Abstract: For pilots, the capacity to cope with anxiety is crucial during a flight since they may be confronted with stressful situations. According to the Big Five Inventory, this capacity can be modulated by two important personality traits: conscientiousness and neuroticism. The former would be related to concentration skills and the latter to the attention bias towards anxiety-provoking stimuli. Given the current development of monitoring systems for detecting the users’ state, which can be incorporated into cockpit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…35 ST articles were found [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. In this context, the simulation of a flight task enables the control of experimental stimuli, such as the addition of engine failures (e.g., [ 43 ]), turbulence (e.g., [ 35 ]) or visibility setting (e.g., [ 30 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 ST articles were found [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. In this context, the simulation of a flight task enables the control of experimental stimuli, such as the addition of engine failures (e.g., [ 43 ]), turbulence (e.g., [ 35 ]) or visibility setting (e.g., [ 30 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Self-Assessment (S) methodologies were employed in 20 ST articles [ 30 , 32 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 47 , 48 , 50 , 53 , 54 , 55 , 57 , 63 ] and in 10 RF articles [ 64 , 65 , 66 , 67 , 69 , 70 , 71 , 73 , 74 , 75 ]. Most of these studies used the Nasa–Task Load index (Nasa-TLX) [ 77 ], which is computed from a simple and strongly validated questionnaire, which is administered after task execution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage between personality, anxiety and responses to different challenging situations has been previously confirmed. In the study by Hidalgo-Munoz et al 29 on pilots where the capacity to cope with anxiety during a flight was similar to the prestart situation when the stressful situation occurred, the results confirmed that neuroticism was linked to cognitive and somatic anxiety. Even when the neuroticism scores were moderate, a positive correlation with the pilots’ subjective anxiety was found while they were carrying out the tasks under the social stressor.…”
Section: Introductionmentioning
confidence: 58%
“…These affective reactions are usually accompanied by physiological responses from the autonomic nervous system (Kreibig, 2010 ). Although these body manifestations can be affected by specific personality traits (Hidalgo-Muñoz et al, 2021 ; Stemmler & Wacker, 2010 ), some physiological patterns seem to be similar across people coping with difficult social interactions, even when different levels of fear to negative social evaluations were present (Chen & Drummond, 2008 ). Therefore, it would be possible to associate physiological response modulations with emotion dynamics in specific interpersonal contexts.…”
mentioning
confidence: 99%